(untitled) (Eurasian Journal of History, Geography and Economics, 2024)
The research aimed to identifyThe effect of the numbered heads strategy on the achievement of fourth year middle school students in historyIn order to achieve the goal of the research, the researcher tested the null hypothesis that concluded in advance that there are no statistically significant differences at the significance level (0.05) between the students of the experimental group who studied according to the numbered heads strategy and the students of the control group who studied in the traditional way. The researcher relied on an experimental design with two experimental and control groups in order to suit the research variables, and on the basis of that, the research sample consisted of fourth-grade middle school students in Al-Karkh Boys’ Secondary School within the first Baghdad Al-Karkh Education Schools, whose number reached (61) students, with (30) students in the group